2019
DOI: 10.1016/j.bone.2018.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Defining osteoblast and adipocyte lineages in the bone marrow

Abstract: Bone is a complex endocrine organ that facilitates structural support, protection to vital organs, sites for hematopoiesis, and calcium homeostasis. The bone marrow microenvironment is a heterogeneous niche consisting of multipotent musculoskeletal and hematopoietic progenitors and their derivative terminal cell types. Amongst these progenitors, bone marrow mesenchymal stem/stromal cells (BMSCs) may differentiate into osteogenic, adipogenic, myogenic, and chondrogenic lineages to support musculoskeletal develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
66
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 63 publications
6
66
0
3
Order By: Relevance
“…This phenomenon, in combination with significantly elevated body weight and left ventricle thickness observed in a prior, similar, study [6], suggests that overall metabolic health may be impaired. These data are consistent with numerous in vitro studies suggesting that FM 550, its components, and structurally related FRs, heighten adiposity at the expense of bone formation [10,[31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This phenomenon, in combination with significantly elevated body weight and left ventricle thickness observed in a prior, similar, study [6], suggests that overall metabolic health may be impaired. These data are consistent with numerous in vitro studies suggesting that FM 550, its components, and structurally related FRs, heighten adiposity at the expense of bone formation [10,[31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Discussionsupporting
confidence: 89%
“…Bone marrow mesenchymal stem/stromal cells (BMSCs) have multipotential to differentiate into osteoblasts, adipocytes, chondrocytes or myoblasts. Molecular factors and differing signaling pathways controlling transcription may alternatively trigger events that direct BMSCs to osteogenesis or adipogenesis [34]. In cases where BMSCs are not directed towards osteogenesis, bone formation may be impaired resulting in deficient bone microarchitecture.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that Macf1 f/f Osx-Cre without rhBMP2 treatment that osteoblasts and adipocytes in bone marrow share a common progenitor, and the dynamic balance between them can influence the density and function of bone. 35 In this study, histological staining of Macf1 deficiency femur displayed an increased accumulation of adipocyte ghosts in situ ( Figure 3E). This phenotype is similar to the observations following the β-catenin and Cbfβ deletion in Osx-expressing cells.…”
Section: Discussionsupporting
confidence: 53%
“…This local environment plays important role in regulating stem cell survival, function and fate [18], and alterations of the microenvironment may impair skeletal stem cells functions, leading to decreased osteogenesis and bone formation [19][20][21].…”
Section: Introductionmentioning
confidence: 99%